2017
DOI: 10.18295/squmj.2016.17.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Culturally-Tailored Breast Cancer Health Education Programme for Arab Women

Abstract: abstract:Objectives: This study aimed to develop and validate a health education programme to encourage breast cancer awareness and early detection behaviours among Arab women. Methods: This study took place between December 2015 and March 2016. The Enabling Systems Raising Awareness model was used to develop a breast cancer health education programme which was subsequently implemented by trained health educators at three female-only fitness clubs in Muscat, Oman. Breast cancer knowledge among 53 women was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(45 reference statements)
2
2
0
Order By: Relevance
“…Students’ knowledge regarding risk factors, symptoms and screenings of different types of cancer improved significantly after the HPC, which is consistent with previous findings (Abuadas & Abuadas, 2020; Alkhasawneh et al., 2017; Ouyang & Hu, 2014). Similarly, a Jordanian study found that the BC educational programme, using various teaching methods, was effective in improving university students’ knowledge regarding BC, its warning signs and risk factors (Alsaraireh & Darawad, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Students’ knowledge regarding risk factors, symptoms and screenings of different types of cancer improved significantly after the HPC, which is consistent with previous findings (Abuadas & Abuadas, 2020; Alkhasawneh et al., 2017; Ouyang & Hu, 2014). Similarly, a Jordanian study found that the BC educational programme, using various teaching methods, was effective in improving university students’ knowledge regarding BC, its warning signs and risk factors (Alsaraireh & Darawad, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…The interactive education about CNCDs significantly improved students’ knowledge of general facts, risk factors, prevention strategies and healthy lifestyles, treatment and complications of CNCDs. This result is supported by a previous studies that used similar interactive methods for education about CNCDs (Alkhasawneh et al., 2017; Alsaraireh & Darawad, 2019; Selvam et al., 2017). Knowledge about common CNCDs could be beneficial for young adults in fighting the epidemic of CNCDs when entering the workforce, starting a career or establishing a new family.…”
Section: Discussionsupporting
confidence: 85%
“…To make initiatives more accessible, they can be launched in frequent venues like schools, media, or supermarkets. Alkhasawneh et al implemented a breast cancer education program for Arab women, raising awareness and participation in screenings [ 25 ]. Serral et al emphasized the importance of educating the population, especially susceptible women, about the benefits and risks of breast cancer screening programs so that they could make informed decisions [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…To be accessible to them, the campaigns could be implemented in places related to their everyday lives, such as schools, the media and/or supermarkets. An example of this was conducted by Alkhasawneh et al [48], who implemented a breast cancer education program for Arab women to increase knowledge of the subject and participation in screenings, and the results were clearly positive. Serral et al [44] invited us to inform the population, focusing on women from the most vulnerable groups, of the benefits and risks of participating in a breast cancer-screening program, so that women can make informed decisions.…”
Section: Discussionmentioning
confidence: 99%